1985
DOI: 10.1152/jappl.1985.58.3.834
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory epithelium inhibits bronchial smooth muscle tone

Abstract: The aim of the present study was to determine whether or not the respiratory epithelium can modulate the responsiveness of bronchial smooth muscle. Paired rings of canine bronchi (4-6 mm OD), in some of which the epithelium had been removed mechanically (by rubbing the luminal surface), were mounted in physiological saline solution, gassed with 95% O2-5% CO2, and maintained at 37 degrees C. The presence or absence of the epithelium was confirmed by histological examination. Removal of the epithelium increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
154
2

Year Published

1986
1986
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(166 citation statements)
references
References 0 publications
10
154
2
Order By: Relevance
“…Besides a direct effect, eosinophils may enhance bronchial reactivity through epithelial damage which has been correlated to airway responsiveness (27). The epithelium may modulate airway responsiveness not only because it acts as a physical barrier to inhaled stimuli (30) but also because it may release relaxing factors (3 1, 32) and inactivate agonists (33).…”
Section: Discussionmentioning
confidence: 99%
“…Besides a direct effect, eosinophils may enhance bronchial reactivity through epithelial damage which has been correlated to airway responsiveness (27). The epithelium may modulate airway responsiveness not only because it acts as a physical barrier to inhaled stimuli (30) but also because it may release relaxing factors (3 1, 32) and inactivate agonists (33).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration-response curve for isoprenaline was shifted about 2 fold to the left in epithelium- Taken together, the published effects of epithelium removal on the pharmacology of airway contractions seem confusing. The initial work by Flavahan et al (1985) in dog bronchi suggested that the response to electrical field stimulation, in particular the duration of the contraction, was increased by epithelium removal. However, later work by Barnes et al (1985) in bovine trachea, Holroyde (1986) and Thompson et al (1986) in cat and guinea-pig trachea, demonstrated no effect of epithelium on the response to electrical field stimulation.…”
Section: Relaxant Agonistsmentioning
confidence: 99%
“…It has had an impact on work with isolated airway preparations where the focus has been on a role for the epithelium in regulation of airway smooth muscle tone. Despite the fact that many of the accumulated observations are negative or contradictory, it has generally been maintained that airway epithelium importantly affects tracheobronchial smooth muscle reactivity (Barnes et al, 1985;Flavahan et al, 1985;Farmer et al, 1986;Finnen et al, 1986;Frossard & Muller, 1986;Goldie et al, 1986;Hay et al, 1986a,b;Holroyde, 1986;Reaburn et al, 1986a,b;Thompson et al, 1986;Tschirhart & Landry, 1986;Nijkamp & Folkerts, 1987). It is understandable that positive results have been searched for and related to the pathology and pharmacology of asthma.…”
Section: Introductionmentioning
confidence: 99%
“…First, airway epithelial cells can inhibit bronchoconstriction through a release of the inhibitory prostaglandins and epithelium-derived relaxing factor [10]. However, because mechanical removal of the epithelium did not alter the effects of TJ-17 and TJ-23, involvement of airway epithelial cells in the drug action seems unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether the release of epithelium-derived relaxing factor is involved in the effects of TJ-17 and TJ-23 [10], the effects of the drug (100 mg . mL -1 ) on acetylcholine (1310 -5 M)-induced contractions between epithelium-intact tissues and the tissues with their epithelial layer removed were compared.…”
Section: Effects Of Epithelial Removal and Pharmacologic Blocking Agentsmentioning
confidence: 99%